Gypsum scaling during forward osmosis process : a direct microscopic observation study - Zhang, Minmin (2014)
This study investigated the effect of supersaturation index (SI), ionic strength, membrane orientation, and antiscalant (AS) addition on gypsum scaling during forward osmosis (FO) desalination. Scaling tests were performed in a cross-flow FO system, and the development of gypsum scalants on FO membrane was directly observed using an optical microscope integrated with the FO filtration cell. Greater surface coverage by gypsum crystals and larger crystal sizes occurred on the scaled FO membranes for feed solutions (FS) with higher SI values accompanying with more severe flux reduction. At fixed Ca2+ and SO_4^(2-) concentrations, reducing the ionic strength of the FS from 0.55 to 0.15 M resulted in longer induction time. Nevertheless, more flux loss and surface coverage by scalants occurred at longer filtration duration for 0.15 M FS due to its greater ion activities and thus higher SI. The active layer facing (AL)-draw solution membrane orientation was found to be prone to internal scaling, which is likely as a result of unfavorable internal concentration polarization of scaling precursors inside the FO membrane support layer. On contrary, the AL-FS orientation had much more stable flux behavior. The current study also demonstrated the effectiveness of AS addition and rinsing under cross-flow conditions for FO scaling control.